2020
DOI: 10.1021/acs.jnatprod.0c00492
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Production and Anticancer Properties of Photoactivated Perylenequinones

Abstract: Hypocrellins and hypomycins are naturally occurring fungal perylenequinones with potential photodynamic activity against cancer and microbial diseases. This project pursued three lines of research. First, the production of perylenequinones was enhanced by investigating the effect of culture medium and light exposure on their biosynthesis. Solid-fermentation cultures on rice medium allowed for enhanced production of hypocrellins as compared to Cheerios or oatmeal medium. Alternatively, increased production of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(79 citation statements)
references
References 57 publications
2
76
0
1
Order By: Relevance
“…Other sources of perylenequinone production could be found. For example, strain MSX60519, isolated from dry leaf litter, was also found to produce hypocrellins [ 16 ], and Li et al [ 61 ] explored an endolichenic strain, Phaeosphaeria sp. 20081120, which could produce HA, HB and other perylenequinones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other sources of perylenequinone production could be found. For example, strain MSX60519, isolated from dry leaf litter, was also found to produce hypocrellins [ 16 ], and Li et al [ 61 ] explored an endolichenic strain, Phaeosphaeria sp. 20081120, which could produce HA, HB and other perylenequinones.…”
Section: Discussionmentioning
confidence: 99%
“…The hypocrellin cluster consists of five main compounds—hypocrellin (1), hypocrellin A (2), hypocrellin B (3), shiraiachrome A (4), and hypocrellin D (5), and their structures are shown in Figure 1 . There is some confusion in the literature over the nomenclature of these compounds, and in this paper the names as defined by Al Subeh et al are followed [ 16 ]. Hypocrellin (1), hypocrellin A (2) and hypocrellin B (3) were first isolated from traditional Chinese medicinal products, which were called “Zhuhongjun” or “Zhuxiaorouzuojun” [ 1 , 17 , 18 , 19 ], and were identified as Hypocrella bambusae (Berk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we evaluated the effect of different fermentation conditions, including varying both culture media and light exposure, on the biosynthesis of perylenequinones, specifically hypocrellins and hypomycins, by the fungus Shiraia -like sp. (strain MSX60519) [ 1 , 2 ]. We showed that the production of these fungal metabolites could be tuned based on media and light exposure.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that the production of these fungal metabolites could be tuned based on media and light exposure. For instance, continuous LED exposure led to enhanced production of hypocrellins on rice medium vs hypomycins on oatmeal medium [ 1 ]. Previously, those classes of secondary metabolites had not been reported from the same fungus, and it was interesting to see how their biosynthesis could be modulated.…”
Section: Introductionmentioning
confidence: 99%